PERANAN GURU DALAM MOTIVASI SISWA DALAM BELAJAR PENDIDIKAN AGAMA ISLAM DI SMP 1 ATAP BATIPUAH KEC X KOTO - Muhammad Hafizh (Sekolah Tinggi Ilmu Tarbiyah (STIIT) Ahlussunnah Bukittinggi, 2019)
This research is a qualitative descriptive study with the title role of the teacher in the learning motivation of Islamic religious education in smp n 1 roof batipuah kec x koto. the purpose of this research is to know how to motivate students gurudalam role in fostering mental and spiritual personality and intellectual students to form good character in the school environment.The results of this study, the data that is descriptive that teachers have not maximizing its role as provider and discipline and moral role model to students in accordance with the burden of teacher competence that personal competence, professional and pedagogical. the expected performance of teachers in educating and teaching to the solution.